2021
DOI: 10.1101/2021.01.23.427888
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tapping into the aging brain:In vivomicrodialysis reveals mirroring pathology between preclinical models and patients with Alzheimer’s disease

Abstract: SUMMARYPreclinical models of Alzheimer’s disease (AD) can provide valuable insights into the onset and progression of the disease, such as changes in concentrations of amyloid-β (Aβ) and tau in cerebrospinal fluid (CSF). However, such models are currently underutilized due to limited advancement in techniques that allow for longitudinal monitoring of CSF akin to methods employed in AD patients. An elegant way to understand the biochemical environment in the diseased brain is intracerebral microdialysis, a meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…This is consistent with CSF t-tau concentrations increasing in the first few days following injury (i.e., probe implantation in our experiments), then reduction over time (Neselius et al, 2012). However, we have previously shown that long-term implantation of our microdialysis probes does not lead to observable neuroinflammation in 3xTg AD mice (Bjorkli et al, 2021). In addition, intracerebral microdialysis is an invasive technique, so it is currently only used in patients requiring neurocritical care, neurosurgery, or brain biopsy (Marklund et al, 2009).…”
Section: Limitations Of the Studysupporting
confidence: 90%
See 3 more Smart Citations
“…This is consistent with CSF t-tau concentrations increasing in the first few days following injury (i.e., probe implantation in our experiments), then reduction over time (Neselius et al, 2012). However, we have previously shown that long-term implantation of our microdialysis probes does not lead to observable neuroinflammation in 3xTg AD mice (Bjorkli et al, 2021). In addition, intracerebral microdialysis is an invasive technique, so it is currently only used in patients requiring neurocritical care, neurosurgery, or brain biopsy (Marklund et al, 2009).…”
Section: Limitations Of the Studysupporting
confidence: 90%
“…Surgeries were based on previously established protocols (Bjorkli, 2021;Bjorkli et al, 2021), but in brief, implantation surgery was performed to insert microdialysis guide cannulas (CMA 7; CMA Microdialysis AB, Kista, Sweden) into the lateral ventricle of mice. Mice were anesthetized with isoflurane gas (4% induction and 1.5-3% maintenance; IsoFlo vet., Abbott Laboratories, Chicago, IL, United States) prior to being fixed in a stereotaxic frame (Kopf Instruments; Chicago, IL, United States).…”
Section: Microdialysis Guide Implantation Surgeriesmentioning
confidence: 99%
See 2 more Smart Citations